Control Effects of Chelonus munakatae Against Chilo suppressalis and Impact on Greenhouse Gas Emissions From Paddy Fields - Fan, Daijia; Zhang, Haoran; Liu, Tianqi; Cao, Cougui; Li, Chengfang (Frontiers in Plant Science, 2020)
Field and pot experiments were conducted to investigate the control effects of parasitoid wasps (Chelonus munakatae Munakata) on striped rice stem borers and their impacts on N2O and CH4 emissions from paddy fields. Three treatments including no insect (NI), striped stem borer (CS) and parasitoid wasp + striped stem borer (CS+CM) were implemented. The abundance of GHG-related microorganisms in soils was determined by absolute real-time qPCR. Compared with NI, CS and CS+CM significantly increased the ratio of dead tillers, inhibited the growth and vitality of rice roots, and decreased the rice grain yield, while they significantly reduced the seasonal cumulative emissions of N2O and CH4 by 17.7–24.6% and 13.6–35.1%, and decreased the total seasonal global warming potential (GWP) by 13.6–34.7%, respectively. Moreover, compared with CS, CS+CM significantly enhanced the growth and vitality of rice roots, decreased the ratio of dead tillers, improved the rice grain yield, as well as increased the seasonal cumulative CH4 emissions and the total seasonal GWP. Principal component analysis indicated that the morphological features of rice roots play a more important role in regulating GHG emissions than GHG-related microorganisms. The results suggested that C. munakatae can effectively control the outbreak of C. suppressalis and alleviate crop damage with acceptably higher GHG emissions. It is concluded that it can be recommended as an effective, environment-friendly and sustainable approach to prevent and control C. suppressalis.